Control of Automatic Beverage Bottle Filling Process Using P and Team Viewer IoT - Imnadir Imnadir; Abdul Khair Junaidi; M. Dalil (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2022)
The development of an on-line process control system in the Industry is a major requirement in the context of the efficiency of machines and improving the quality of production during the Covid-19 period. As well as in the learning system and practicum students are required to be able to study independently, and lecturers must be able to develop themselves in on-line learning methods. The on-line learning process is not just to transfer learning modules to students, but must be able to guide students in an unlimited time, whenever students need an explanation of the material provided. TeamViewer is an application that provides a solution that is used to remotely control another PC or laptop. By knowing the ID and password are provided by TeamViewer on the PC that want to remote. Then, it just entered the TeamViewer application installed on the PC. The use of this team viewer was tested against the control of the beverage bottle filling process. The result is that by using Android the process of controlling beverage bottle filling. It turns out that, it can be operated to fill beverage bottles for different size, namely by setting the data delay on the program 3.2 seconds for the 120 ml bottle size, 4.0 seconds for the 200 ml bottle size, and 5.0 seconds for the bottle size of 300 ml.